2020
DOI: 10.21203/rs.3.rs-107087/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Child Injuries in Lebanon: Assessing Mothers Injury Prevention Knowledge Attitude and Practices – A Cross Sectional Study

Abstract: Background: Childhood injury is a neglected public health problem. This study aims to describe the patterns of childhood injury and to determine mothers' Knowledge, Attitude, and Practices (KAP) towards childhood injury prevention in Lebanon. Methods This cross-sectional study recruited working and non-working mothers of children aged 0-10 years from multiple sites (i.e. medical center, private clinic, healthcare facility, refugee camp) to cover all socioeconomic backgrounds. A self-administrated questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…Comparing our study with the study conducted by Al-Hajj S et al [10] in Lebanon, it is found that the respondents were slightly older than the present study population (32.7 vs.28.8 years). The education levels were also higher in their study with more than 56.9% having a university degree as compared to 34.5% in the present study.…”
Section: Discussioncontrasting
confidence: 47%
“…Comparing our study with the study conducted by Al-Hajj S et al [10] in Lebanon, it is found that the respondents were slightly older than the present study population (32.7 vs.28.8 years). The education levels were also higher in their study with more than 56.9% having a university degree as compared to 34.5% in the present study.…”
Section: Discussioncontrasting
confidence: 47%
“…On the same way, study done by Al-Hajj et al (13) in Lebanon indicating that mothers had poor knowledge about different aspects of home accidents.…”
Section: Resultsmentioning
confidence: 69%
“…Similarly, Anwar et al (16) carried out study in Beni-Suef showing that mother age was significant predictor of knowledge score. On the contrary, Al-Johani et al (13) done study in EL-Madinah City revealed that parent's ages were not significantly associated with their knowledge.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation